The Fc Orth (SA) final examination The short-term outcome of hip revision arthroplasty with Trabecular Metal™ components and augments - Noconjo, Lubabalo (Division of Orthopaedic Surgery, 2021)
Background: Highly porous Trabecular Metal™ acetabular components are increasingly being used in revision hip arthroplasty as they facilitate ingrowth, provide a useful mechanism to deal with bone loss and may decrease the risk of infection. The purpose of this audit was to describe: 1) the short-term radiological outcomes of revision hip arthroplasty with Trabecular Metal™ components and augments. 2) the total number of hip arthroplasty surgeries over five years, and indications for revision. Methods: A retrospective folder and radiograph review of all patients who had revision total hip arthroplasty (THA) at a tertiary level hospital from February 2012 to February 2017 was done. Results: There were 979 THAs performed over the period – 863 (87%) primary THAs, and 116 (12%) hip revision cases performed in 107 patients. Of the 116 (107 patients) hip revisions, there were seven (6%) re-revisions in five patients. Trabecular Metal™ was used for revision in 16 hips (14 patients), which is 13.7% of the total 116 revisions. There were ten females and four males with an average age of 61 years. The average duration of follow-up in this group was 18.5 months (1.5– 39.2). In these 16 Trabecular Metal™ hips, there were three (18.7%) early failures of fixation due to technical errors. The indications for revision were aseptic loosening 67 (58.6%), septic loosening 11 (9.5%), liner wear 18 (15.5%), periprosthetic fracture five (4.3%), other 15 (13%). Conclusion: In our institution, Trabecular Metal™ revisions had a 18.7% early failure rate due to technical error. 12% of the arthroplasty is revision surgery. The indications for revision are similar to published literature.